MORE THAN TOLERANCE: THE ISLAMIC CALL FOR INTERRELIGIOUS REVERENCE - Quadir, Tarik (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
What is the Qur’ān’s stance towards religions other than Islam? May non-Muslims find salvation? If they do, as the Qur’ān seems to suggest in verses 2:62 and 5:69 explicitly, how does that make sense in light of verses which seem to deny this possibility for those who subscribe to any understanding of God which differs from that of Islam? We look for the answers mostly in the verses that are related to Judaism, Christianity, their adherents, religious diversity, and the ultimate criterion for salvation. We conclude that the Qur’ān takes a generous stance towards the other two Abrahamic traditions and their adherents; moreover, verses 2:62 and 5:69 are fully justified in view of the nature and function of the primordial human nature (fitrah), the heart, and the true meaning of submission to God. In short, the Qur’ān’s stance towards other religions goes well beyond mere tolerance.